ANALISA TINGKAT KEPUASAN ALUMNI TERHADAP KUALITAS PELAYANAN FAKULTAS EKONOMI UNIVERSITAS PEKALONGAN - Muhammad Shofiyuddin; Amalia Ilmiani (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
This study aims to analyze customer satisfaction (collegiate) for services provided in college. The method  of  study  is  by  using  questionnaire  with  sample  of  population  taken  from  students  of Economic Faculty of Pekalongan University who graduated in September 2012. This research is a descriptive study, the type of design conclusive that aims to describe the character or function of the research on a group. The results of this research find that satisfaction of service perceived by the students of the Faculty of Economics, University of Pekalongan is in conformity with what is expected  however  to  laboratory  facilities  is  very  important  to  note  and  it  is  important  to  be completed.  Keyword: Students’ Satisfaction, service quality.